Impact of maritime transport and connectivity on Natuna Regency’s economic development - Hidayat Kamarul; Asdar Muhammad; Jompa Jamaluddin; Langas Siahaan Denny (BIO Web of Conferences)
This study investigates the influence of maritime transport, connectivity enhancements, and governmental policies on the economic development of Natuna Regency from 2016 to 2021. Using a mixed-methods approach combining quantitative analysis and qualitative insights, the research explores the factors shaping regional economic growth. The findings highlight the pivotal role of maritime infrastructure in facilitating trade and enhancing logistical efficiency, complemented by advancements in digital connectivity. Effective governmental policies, including regulatory reforms and fiscal incentives, emerge as critical drivers in fostering an environment conducive to private sector investment and entrepreneurial activity. The study underscores the interconnected nature of these factors in bolstering economic resilience and sustainability amid global uncertainties. Recommendations include sustained investments in maritime infrastructure, digital connectivity, and adaptive policy frameworks to maximize Natuna Regency's maritime potential. This research provides strategic insights for promoting sustainable economic development in Natuna Regency and similar maritime-dependent regions.